(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Identification of areas favorable for the localization of ore-bearing rocks is the pathway to reveal new ore fields and deposits. In most cases, not all ore-controlling structures are revealed, often many important elements are hidden, and therefore the structural position of ore taxa of different scales is interpreted incorrectly, which does not contribute to the discovery of similar realms and, accordingly, new ore accumulations. Recognition of weak lineaments and ring structures is of particular importance for elucidating the complete picture of the structural position of the deposit. The studies carried out made it possible to detect cryptostructures, to group ore fields according to their geological and structural locations. It is revealed the industrial deposits of the region are localized in three typical settings that are ring and arc-shaped structures, zones of large disturbances and outside of the ring structures, and zones of big faults and related to the faults of local scale (second–third order). The main part of deposits are related to the first geological and structural type. This type includes the large Teghut porphyry copper deposit as well, but the rest are of medium scale and belong to copper pyrite type (Shamlugh and Alaverdi), pyrite-polymetallic (Akhtala) and gold-polymetallic (Armanis) formation types. Each ring structure contains one industrial object. The only Martsiget ore field is related to the zone of the large Martsiget-Lalvar fault where three small allocations have been identified containing a small amount of gold and polymetallic ore reserves in all. Small chalcopyrite-type deposits of the Aghvi, Archut, and Mghart, in which the main value represent the gold reserves, are confined to local-scale faults. The identified pattern of localization of industrial ore accumulations made it possible to allocate new favorable ore formations, which are allocated in the southern part of the region and related to the ring structures located in the Pushkino-Acharkut fault zone. A predictive assessment of the expected ore accumulations is given. The use of the information obtained should have a positive impact on the effectiveness of geological explorations.